Encouraging Autonomous English Learning in Overcrowded Online Class of Elementary School during Pandemic - Misbachuddin Akbar Putra (Yayasan Visi Intan Permata, 2021)
During the Covid-19 pandemic, most schools have been closed by the government to prevent Coronavirus spread. It mandates students to learn and teachers to teach from home. This condition is also illustrated in the English classes for the first, second, and third grades of SDN Sedatigede 1. With more than 80 students in one class, it can be assumed that each English session is overcrowded. A pupil may have a slim chance to learn with a teacher’s guidance in an overcrowded class. Therefore, this analysis attempts to discover a way for students to learn a language independently using language learning program accessible on the internet. This research then reveals three language learning services believed to be suitable for elementary school students. From these results, this study provides solutions for the teachers to motivate their students to apply these resources for learning English autonomously and with minimal teacher guidance. Further research is required to find autonomous learning ways in offline media for students with no access to the internet and proper ways for teachers to fulfil their role as a motivator in this pandemic era.